The CAP mid-term review is affected by the US Farm Bill - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
At the EU Agricultural Council meeting of May 27th 2002 the French delegation...